The selection of conservation areas in the Brazilian Atlantic forest: review of studies for spatial prioritization - Pezzi D'Arrigo, Rosana Cristina (2020)
The Atlantic Forest (AF) has a history of uninterrupted environmental degradation which is the oldest and most continuous in Brazil. On the other hand, it was the AF biome where the first protected areas were demarcated in Brazil. The AF is broadly studied in the field of Biological Conservation. The methodologies for evaluating, selecting and prioritizing areas for allocating conservation strategies, in the context of the Systematic Planning for Conservation (SPC), have been developed since the year 2000. A bibliographic review of the research activity related to the SPC and the application of spatial prioritization methods for conservation in the Brazilian Atlantic Forest was carried out here. In this research, twenty-one academic and two non-academic studies were surveyed. There is a tendency of the surveyed studies, mainly academic ones, to use specific taxonomic groups as species of terrestrial vertebrates as indicators of biodiversity. Low setback of studies that use the SPC and the methods for spatial prioritization for conservation in Brazilian AF in conservation actions is also observed in most studies that adopt these methodologies.